IMPLEMENTASI PENDEKATAN PROSES DALAM PEMBELAJARAN MENULIS CERITA PENDEK - Halidjah, Siti (Universitas Tanjungpura, 2017)
AbstractÂ This study aims to gain a deep understanding of the implementation of the process approach in teaching writing short stories on students of PGSD FKIP Untan. This study used a qualitative approach. Sources of data in this research is learning events to write a short story using a process approach. Research procedures used in this study is the planning, implementation, data analysis, and report writing. Data collection technique used is the technique of direct observation and document scrutiny. Data collection tool used is a field record sheets and documentation with regard to the learning process and learning outcomes. This research data analysis begins with data collection, data reduction, data presentation, and conclusion / verification. Based on the results and discussion of this research can be concluded that the process approach can improve the skills of students to write short stories. This increase can be seen from both process and product. Learning to write by following the steps in the process approach can help lecturers provide variety and stimulation in a given assignments to write short stories. In the process of improvement can be seen from the learning process with the creative writing process approach in the activities of the students and the classroom situation in learning creative writing poetry, while in terms of products increase student skills to write short stories.Â Keywords: process approach, teaching writing, short story